Effectiveness of Early Mobilization on the Pain of Post Laparatomy Patients - Daryani Daryani; Fitri Suciana; Marwanti Marwanti; Sunardi Sunardi (Indonesian Journal of Global Health Research, 2023)
The purpose of the study was to determine the effectiveness of early mobilization on the pain of laparotomy postoperative patients. This type of research is called quantitative research. The design in this study is pre-experimental, with a one-group pre-test-post-test design. Sampling using purposive sampling techniques The number of respondents was 15 post-laparotomy patients. Data analysis was conducted univariately and bivariately (Wilxocon Signed Rank Test). The results of the study found patient characteristics: the average age was 36.8 years, the gender was mostly women (66.7%), the work of most housewives (46.7%), and education was mostly high school (53.3%). The results of bivariate analysis found that the pv value was 0.000 with α: 0.05. Conclusion: Early mobilization is effective in reducing pain in post-laparotomy patients.